Abnormal pattern of integrin expression at the implantation window in endometrium from fertile women treated with clomiphene citrate and users of intrauterine device - Gonzalez, R R; Palomino, A; Vantman, D; Gabler, F; Devoto, L (Early pregnancy, 2001)
Determine quantitative expression of endometrial integrins that reflect receptivity during implantation window in fertile women treated with clomiphene citrate (CC), and in intrauterine device users (IUD) as compared to fertile controls. Comparative study of the quantitative expression of a1, a4, av and b3 integrins in epithelial and stromal cells in mid-secretory endometrium of CC treated fertile women, IUD users and controls. All subjects included in this study had regular and ovulatory menstrual cycles. Ten women treated with a daily dose of 50 mg of CC. Six women T-Cu device users and nine fertile controls. Age ranges for all groups were similar, 29-41 years old (mean 36.3). Tissue samples were taken at the mid-secretory phase or implantation window. A histological dating of the endometrial biopsies was assessed according to Noyes criteria. Ovulation was assessed by repeated transvaginal ultrasonography. The expression of a1, a4, aV and b3 integrins in dispersions of epithelial (EEC) and stromal (ESC) cells isolated from endometrial biopsies was quantitatively determined by flow cytometry using specific monoclonal antibodies. Immunohistochemistry was also used to detect integrin expression. Biopsies from CC-treated women had a high incidence of out-of-phase endometria. Interestingly, CC-treated women over-expressed a1, aV and b3-ESC integrins and under-expressed b3-EEC subunit (P<0.05). IUD users over-expressed the a1-EEC and under-expressed a4-ESC (P<0.05) at the time of the implantation window. CC treatment in fertile women provokes a high frequency of out-of-phase endometrium and desynchronises the expression of endometrial integrins at the implantation window. The epithelial b3 integrin was under-expressed in all CC-treated patients. The T-Cu intrauterine device alters endometrial receptivity by a different mechanism independent of the expression of the epithelial b3 integrin. However, both CC and IUD use alter the expression of some epithelial and stromal integrins during the implantation window.